Clinical analysis in patients with SPG11 hereditary spastic paraplegia - Kang, You-Ri; Nam, Tai-Seung; Kim, Jae-Myung; Kang, Kyung Wook; Choi, Seong-Min; Lee, Seung-Han; Kim, Byeong C.; Kim, Myeong-Kyu (Frontiers in neurology, 2023)
To analyze the clinical phenotype of hereditary spastic paraplegia (HSP) caused by mutations (SPG11-HSP). Among the 17 patients with sporadic HSP who performed whole exome sequencing analysis, six were diagnosed with SPG11-HSP. The clinical and radiologic findings and the results of the electrodiagnostic and neuropsychologic tests were reviewed retrospectively. The median age at onset was 16.5 years (range, 13-38 years). Progressive spastic paraparesis was a core feature, and the median spastic paraplegia rating scale score was 24/52 (range, 16-31 points). Additional major symptoms were pseudobulbar dysarthria, intellectual disability, bladder dysfunction, and being overweight. Minor symptoms included upper limbs rigidity and sensory axonopathy. The median body mass index was 26.2 kg/m (range, 25.2-32.3 kg/m ). The thin corpus callosum (TCC) was predominant at the rostral body or anterior midbody, and the ears of the lynx sign was seen in all. The follow-up MRI showed the worsening of periventricular white matter (PVWM) signal abnormalities with ventricular widening or the extension of the TCC. Motor evoked potentials (MEP) to the lower limbs showed an absent central motor conduction time (CMCT) in all subjects. The upper limb CMCT was initially absent in three subjects, although it became abnormal in all at the follow-up. The mini-mental state examination median score was 27/30 (range, 26-28) with selective impairment of the attention/calculation domain. The median score of the full-scale intelligence quotient was 48 (range, 42-72) on the Wechsler Adult Intelligence Scale test. Attention/calculation deficits and being overweight as well as pseudobulbar dysarthria were common additional symptoms in patients with SPG11-HSP. The rostral body and anterior midbody of the corpus callosum were preferentially thinned, especially in the early stage of the disease. The TCC, PVWM signal changes, and MEP abnormality worsened as the disease progressed.